Integrasi nilai karakter lokal dalam pengembangan bahan ajar IPS untuk meningkatkan wawasan kebangsaan siswa - El Rizaq, Agung Dwi Bahtiar; Sarmini, Sarmini; Sunarto, Sunarto (Jurnal Teori dan Praksis Pembelajaran IPS, 2020)
Knowledge and cognitive development of individuals come from socio-cultural sources that are around themselves. This article is intended to examine the use of local character values in the development of social studies teaching materials in schools. The method used is the 4-D model Thiagarajan, which has a soft, (1) Determine, (2) Design, (3) Develop, and (4) Disseminate. From the research process, a significant difference is presented between learning before using character values and after using local characters. This is discussed by the difference in the pre-test and post-test values after there is a use of character values in the social studies learning process, the t-count value indicates the value is higher than the t-table value, 1.7> 1.685 for 5%. The n-gain pre-test and post-test values were 0.58 in the medium category. These values indicate the value of local characters has a significant increase in improving student learning outcomes. From the results of this test, it is recommended for experimental research with explanatory designs to illustrate the consistency of local characters in the knowledge of students on the subject of a nationalism insight.DOI: 10.17977/um022v5i12020p019